GOLAGA TOURIST ATTRACTIONS MANAGEMENT STRATEGY - Praptiningsih (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This study aims to analyze the management of Golaga's natural tourist attractions. The research method used was a qualitative approach, with data collection techniques including observation, in-depth interviews, and documentation. Data analysis was conducted using the POAC (Planning, Organizing, Actuating, and Controlling) management theory. The research results show that Golaga tourism management has implemented the POAC management principles as proposed by George R. Terry. In the planning aspect, management focuses on digital promotion, collaboration with travel agents, community empowerment, and planning the addition of artificial gravity-based attractions. In the organizing aspect, the organizational structure of PERUMDA Owabong has been clearly and systematically structured, starting from the board of directors to the implementing units in the field. The actuating aspect is realized through the involvement of local communities as a workforce of 80–90%, the implementation of excellent service training, and the empowerment of local MSMEs. Meanwhile, the controlling aspect is carried out through routine evaluation of facilities, digital promotions, and monitoring of tourist reviews on social media and other online platforms. The implementation of this management has had a positive impact on increasing the number of tourist visits and achieving Golaga's revenue, which reaches billions of rupiah per year. Furthermore, factors influencing the management of Golaga's tourist attractions demonstrate a combination of potential and challenges. From an attraction perspective, the uniqueness of the approximately 1,200-meter-long ancient lava cave is the main attraction, supported by modern man-made attractions. However, the potential for educational and cultural tourism has yet to be optimally and sustainably developed. In terms of accessibility, Golaga's location is relatively easy to reach, although limited local transportation and buggy fleets remain a challenge. Basic amenities are adequate, but internet connection quality in the cave area remains limited. Meanwhile, additional services and tourism activities are well developed, but the availability of integrated tourism packages still needs to be improved. Therefore, Golaga's development strategy needs to be directed at strengthening integrated tourism packages, improving supporting infrastructure, and empowering the community in a sustainable manner to maximize tourism potential and improve the economic welfare of the Siwarak Village community.